Alien abduction: disruption of native plant-pollinator interactions by invasive species - Ghazoul, Jaboury (Biotropica, 2004)
The indirect impacts of Shorea siamensis-logging on the reproductive ecology of Dipterocarpus obtusifolius, a self-incompatible butterfly-, moth-, and bird-pollinated tree, were studied in tropical dry forest in Thailand. Pollinator activity at D. obtusifolius trees and subsequent seed production were recorded in three forest areas subject to differing intensities of S. siamensis extraction. The pollinator and plant understory communities in these areas were also noted. Forest areas subject to high S. siamensis extraction intensities had very high understory flowering plant cover, dominated by the exotic invader Chromolaena odorata. Activity of butterfly pollinators at D. obtusifolius trees decreased in these disturbed areas, although their abundance remained comparable to other forest areas subject to only moderate or no extraction. For sphingid moth pollinators, there was no difference across differentially disturbed forest areas in either abundance or in the proportion bearing pollen. Pollinator activity by birds increased at highly disturbed locations but was not sufficient to offset a decline in overall pollinator activity at D. obtusifolius canopies in areas of heavy S. siamensis extraction. Thus, extraction of S. siamensis indirectly affected the pollination of D. obtusifolius, primarily by causing changes in the foraging behavior of butterfly pollinators rather than their abundance. A shift in the relative abundance of floral nectar resources from the canopy to the understory, a consequence of S. siamensis extraction and invasion by odorata, led to a parallel shift in foraging location of the principal diurnal pollinators, the butterflies, toward the understory. Despite reduced pollination at disturbed sites, behavioral changes did not translate into a D. obtusifolius seed set effect, possibly because pollination by birds (or moths) at the disturbed site compensated for reduced butterfly pollination.